"Sign of the kiss" in dermatitis caused by vesicant beetles ("potós" or Paederus sp.) - Vidal Haddad Junior (Sociedade Brasileira de Dermatologia, 2014)
The cosmopolitan beetles of the Paederus genus (potós) cause a severe dermatitis when the insect is crushed against the skin of exposed areas (the cervical region is the most affected). Toxins (pederin and others) from the hemolymph of the insect cause plaques and/or bizarre, linear lesions with erythema, edema, blisters, pustules, crusts and exulcerations. There may be a burning sensation and severe conjunctivitis. Lesions disappear after 10 days and may leave hyperchromic macules. Treatment is made with topical corticosteroids and intensive washing.